Aesthetic reading as a problem in mid-20th century Swedish educational policy - Lindsköld, Linnéa; Dolatkhah, Mats; Lundh, Anna (University of Borås, 2020)
This study aims to identify and analyse how aesthetic reading was problematised in Swedish educational policy 1940-1962, in order to create a better understanding of the politics of reading in an era that has been of great importance for how reading is understood in contemporary Sweden. The empirical material consists of reports from three school commissions, laying the foundation for the new compulsory and comprehensive school that was introduced in 1962. The reports have been analysed using a discursive methodological framework, focussing on problematisations of aesthetic reading. The main problem that aesthetic reading was meant to solve, according to the analysis, was a lack of aesthetic taste. There is a shift in emphasis during the period from problematisations of what to read towards problematisations of how to read. Thus, the solution to the problem of aesthetic reading during the period transformed from a governing of taste to a governing of skills. Educational and cultural policy shares the problematisation of aesthetic upbringing, made possible by its roots in modernist ideas of general character formation and the ideals of free public education. We argue that research on the politics of reading in Sweden can be reinvigorated by exploring the governance of cultural practices emanating from policy fields other than explicit cultural policy.